Analysis on surface damage of M50 steel at impact-sliding contacts. (October 2020) - Wang, Che; Zhang, Chuanwei; Gu, Le; Bi, Minglong; Hou, Pingping; Zheng, Dezhi; Wang, Liqin
Abstract: The surface damage of M50 steel at impact-sliding contacts was investigated considering thermal effects of materials. The mechanical response and thermal response of materials were analyzed using the thermo-elasto-plastic finite element method. The heat dissipation resulting from the frictional work and plastic deformation work were determined and the effects of impact and sliding velocities were discussed. The results indicated that at low impact and sliding velocities, the temperature rise resulted primarily from the frictional work, leading to thermal softening of the near-surface material. At high impact and sliding velocities, the material underwent high-strain-rate plastic deformation. Consequently, the temperature increased further due to the heat of strain energy dissipation, which promoted thermal softening and led to surface damage of M50 steel. Highlights: Thermal softening of M50 steel at impact–sliding contacts is analyzed. Plastic strain in near-surface material is generated. High temperature is caused by both the frictional heat and strain energy. Influence weight of sliding and impact velocities are determined.